User-Centric Waste Management Through Reward-Based Digital Systems - Ama Muzni Mahmudi; Teddy Mantoro (Poltanesa, 2025)
The effective management of household and urban waste is a critical challenge in achieving sustainability within the fields of waste management and circular economy practices. Traditional waste sorting systems face inefficiencies due to low user participation, limited accountability, and inadequate transparency in tracking and reporting waste contributions. This research addresses these challenges by introducing a reward-based digital platform that incentivizes users to sort and deposit waste at designated collection points. The platform assigns points based on the type and quantity of waste submitted, tracks contributions, and provides detailed reports to users, fostering transparency and trust. The proposed solution demonstrates potential to increase user engagement, improve waste sorting accuracy, and enhance reporting capabilities, supporting the transition toward sustainable and circular waste management systems.